PENGARUH PREPARASI SALURAN PASAR TERHADAP KEBOCORAN APIKAL PADA OBTURASI SALURAN AKAR MENGGUNAKAN JENIS SILER YANG BERBEDA - , Sri Darmayanti, drg. R. Tri Endro Utara, M.Kes., Sp.KG ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research was to evaluate the effect of post canal preparation on the apical leakage of root canal obturation using different sealers. A total of 42 single rooted maxillary premolars were randomly divided into 2 groups of 21 and root canal prepared. Each group was subdivided into 3 subgroups of 7 which were obturated using zinc oxide eugenol sealer (group IA), resin sealer (group IB) and calcium hydroxide sealer (group IC) Group I was then post canal prepared but not with group II. All specimen root surfaces were covered with sticky wax and finally with nail paint except 2mm from apical foramen. Each specimen was immersed in methylene blue dye and centrifuge for 3 minutes 800 rpm. All groups were then decalcified using 5% nitric acid solution for 3 days, dehydrated using 80% alcohol solution for 12 hours, 90% alcohol for 1 hour and finally cleared in 100% methyl salicylate solution for 2 hours. Dye penetration was assessed using stereo microscope to find the longest dye penetration from apex to occlusal. The result of two-way ANAVA and LSD showed no effect of post canal preparation on apical leakage using different sealers (p>0,05), and there was effect of sealer types on apical microleakge (p<0,05) where zinc oxide eugenol sealer of the group with post canal preparation was the greatest, followed by Calcium hydroxide sealer and finally resin sealer.